Analisis Determinan Tingkat Pertumbuhan Total Aset Perbankan Syariah di Indonesia - Kristianingsih Kristianingsih; Rinita Salsa Ziljiani; Koernia Purwihartuti; Hennidah Karnawati; Setiawan Setiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Total assets of sharia banking in Indonesia ranked the 9th largest Islamic banking assets in the world with a total asset value of USD 37.7 billion and contributed 6.1% market share in the 3rd quarter of 2020. Despite that, the growth of Islamic banking assets experienced a slowdown from 2016 to 2020. Accordingly, it is important to identify critical factors for the growth of Islamic banking assets to accelerate the growth of the industry. This study examines the determinants of the growth of sharia banking assets which are represented by internal variables of TPF, FDR, and CAR, and external variables of GDP, Inflation, and BI Rate using the Error Correction Model (ECM) approach with secondary data samples from all BUS and UUS in Indonesia. The results showed that in the long term and short term, TPF and FDR variables have a positive and significant effect on the total assets of sharia banking, while the CAR and Inflation variables have a positive and insignificant effect, and the GDP and BI Rate variables have a negative and insignificant effect.